International economics / James Gerber - Gerber, James
International Economics uses real-life applications to cover both the macro and micro components of international economics. The text illuminates economic institutions and policies, as well as recent developments in the global economy, without requiring the use of higher-¿level math. In addition, the text has a flexible approach, which includes self-¿contained chapters and comprehensive coverage, allowing readers to adapt its concepts to a wide range of possible uses. The 7th Edition includes a number of enhancements, such as updated tables and graphs, new case studies, and revised discussion of relevant topics.